(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Excessive screen time in early childhood has become a major public health concern, especially after the COVID-19 pandemic. This review of the literature critically analyzes current studies examining the effects of screen time on cognitive, language, social-emotional skills, physical growth, and preparedness for school in children aged 0–6 years. Five significant peer-reviewed studies released from 2022 to 2023 were examined, comprising systematic evaluations and forward-looking cohort studies. Results consistently show correlations between heightened screen time and setbacks in language development, diminished academic preparedness, reduced quality of parent-child engagement, and possible cognitive and social-emotional weaknesses. Despite methodological constraints, causality cannot be definitively determined, Accumulating evidence backs suggestions for controlled, age-appropriate, and monitored screen usage. This analysis compiles existing evidence, highlights research shortcomings, and explores effects on clinical practice, parental support, and policies for early education.